(untitled) (American Journal of Multidisciplinary Research and Innovation, 2023)
Economic factors in the international scene have attracted trained and qualified health personnel in other countries. The mass exodus has been happening at an alarming rate, resulting in disadvantaged countries losing effective hospital staff. Staff turnover has been witnessed in Government administered hospitals in Zimbabwe. Both low and high staff turnover has proven to affect the healthcare system. This is evident in the poor health service that is being delivered after qualified and experienced doctors, nurses and other related personnel have left their work places in search of better opportunities and greener pastures. The study gathered findings from related literature and distributed questionnaires around selected hospitals in an attempt to evaluate and assess the effects of high staff turnover in Zimbabwean hospitals. Thus, a survey on the results of being short staffed due voluntary hospital staff turnover has shown the negative effects of staff turnover in Zimbabwean hospitals. The study included four government hospitals (GH) as case studies, these are; Chivhu, Sadza, Kotwa and Marondera Hospitals. The study reviewed that 95% of the respondents indicated that there was a record of staff turnover at their respective hospitals. The research results showed that nurses constituted the most staff members leaving government hospitals, making up 29.49% of the total turnover in the four GH involved in the study. The destination for those nurses and other medical practitioners was regarded as ‘g mainly regarded as ‘greener pastures’ in the United Kingdome effects of staff turnover was the shortage of qualified and experienced staff members in hospitals in Zimbabwe which affected the quality-of-service delivery. This article gives in detail the objectives, results and recommendations for the topic in question.